HIRARC Risk Control in Agricultural Machinery Production (Case Study: PT. XYZ): Pengendalian Risiko HIRARC dalam Produksi Mesin Pertanian (Studi Kasus: PT. XYZ) - Albaharits, Adnan; Tranggono, Tranggono; Novita Sari, Rizqi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Occupational health and safety remains a critical concern in manufacturing operations where unrecognized hazards contribute to workplace accidents. Specific Background: In agricultural machinery production, the production department still encounters multiple hazards, limited supervision, and low compliance with safety standards despite the establishment of a dedicated safety unit. Knowledge Gap: Prior studies applying Hazard Identification, Risk Assessment, and Risk Control (HIRARC) predominantly focus on identification and assessment stages, with limited integration of root cause analysis for high and extreme risks. Aims: This study aims to systematically identify hazards, assess risk levels, and determine appropriate control measures through an integrated HIRARC and Fishbone approach. Results: The analysis identified 27 risk events, comprising 10 low, 8 medium, 8 high, and 1 extreme risk, with the most critical risk associated with crane-based material handling operations requiring immediate control prioritization. Root causes of high and extreme risks were linked to human, machine, method, material, and environmental factors. Novelty: The study introduces an integrated HIRARC–Fishbone framework to prioritize risk control while simultaneously identifying root causes in manufacturing processes. Implications: This approach provides a structured basis for prioritizing critical risks and supports systematic accident prevention strategies, contributing to improved occupational safety performance in industrial environments. Highlights: Twenty-seven hazard-related activities were classified into four risk categories. Crane-based material handling emerged as the most critical hazard source. Human-related factors dominated the root causes across high-risk scenarios. Keywords: Fishbone Diagram, HIRARC, Manufacturing Industry, Occupational Health and Safety